Aprendizagem baseada em problemas na formação inicial do professor de matemática: um experimento - Zimmermann, Samuel Sonego (2019)
The present research has as a problem to investigate what are the learning potentials of a group, composed of four students of the Mathematics Degree course at the Federal University of Santa Maria (UFSM). Through a didactic sequence along the lines of Problem Based Learning (PBL) in teaching functions. Altogether, 11 meetings were held, one per week in the afternoon shift, with an average duration of two hours. The elaborated activities are composed by the concept of affine functions, quadratic and applications. As a theoretical contribution, John Sweller's Theory of Cognitive Load was adopted. Before the development of the study, the group answered an initial questionnaire to verify previous knowledge about functions and PBL, and a second questionnaire at the end of the didactic sequence. As a tool for data collection, the researcher's diary and a spreadsheet called the photograph of the moment were created, serving as support to fulfill the objective. Therefore, a qualitative research-action was carried out. Analyzing the first questionnaire, it was possible to identify the lack of knowledge about active methodologies, the concept of open problem. By comparing the researcher's diary and the second questionnaire with the first, it was possible to infer that PBL has so many complicating factors - time, teacher preparation, problem construction, fear of using new methods and students' difficulties - such as facilitators - interdisciplinarity, professional preparation, initiation into the scientific method, practical activity and group work.